Reconhecimento de sentenças arbitrais estrangeiras nos BRICS, em Israel e nos Estados Unidos: uma análise da exceção da ordem pública sob o enfoque da diversidade de culturas jurídicas - Mark David Martin (2019)
The aim of this research is, through the perspective of comparative law, to analyze the views and interpretations of public policy as a limit to the recognition and enforceability of foreign arbitration decisions in countries known as BRICS (Brazil, Russia, India, China, South Africa). This dissertation also compares its object of study with the perceptions of public policy in the legal system of Israel and the United States of America, seeking elements of distinct nuances of legal culture that shape the visions of their domestic courts in the treatment of recognition and enforcement of foreign arbitral decisions. The purpose of this research is to examine the cases of foreign arbitral awards in the countries studied in order to demonstrate a path, little explored by private and comparative international law, to objectively identify the position, whether liberal or restrictive, of these countries with respect to the circulation of foreign arbitral awards and if it would be possible to draw conceptual lines of public order and give a minimum prediction of the legal treatment given by each of these countries to the limiting principle of public order. Regarding the research methodology, based on an exploratory research, the domestic treatment given by these countries to the concept of public order and the juridical-cultural elements that create their respective jurisprudential contexts were verified. Thus, like the macro-structure created by the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958, the critical-comparative analysis of this dissertation makes it possible to consolidate new avenues for foreign arbitration decisions on a transnational scale. In order to verify the multiple interpretations of the principle of public order in the countries studied, from restrictive to very broad interpretations, this study points to the need for future paths that can lead to the construction of bridges of interaction between legal systems, allowing greater fluidity of foreign arbitral awards and of international trade.